Separation by dielectrophoresis of dormant and nondormant bacterial cells of Mycobacterium smegmatis - Zhu, Ke (American Institute of Physics, 2010)
The dielectrophoretic behavior of active, dead, and dormant Mycobacterium smegmatis bacterial cells was studied. It was found that the 72-h-old dormant cells had a much higher effective particle conductivity (812±10 μS cm(−1)), almost double that of active cells (560±20 μS cm(−1)), while that of dead (autoclaved) M. smegmatis cells was the highest (950±15 μS cm(−1)) overall. It was also found that at 80 kHz, 900 μS cm(−1) dead cells were attracted at the edges of interdigitated castellated electrodes by positive dielectrophoresis, but dormant cells were not. Similarly, at 120 kHz, 2 μS cm(−1) active cells were attracted and dormant cells were not. Using these findings a dielectrophoresis-based microfluidic separation system was developed in which dead and active cells were collected from a given cell suspension, while dormant cells were eluted.